Next-generation sequencing of hereditary hemochromatosis-related genes: novel likely pathogenic variants found in the Portuguese population - Faria, Ricardo (2020)
Hereditary hemochromatosis (HH) is an autosomal recessive disorder characterized by excessive iron absorption resulting in pathologically increased body iron stores. It is typically associated with common HFE gene mutation (p.Cys282Tyr and p.His63Asp). However, in Southern European populations up to one third of HH patients do not carry the risk genotypes. This study aimed to explore the use of next-generation sequencing (NGS) technology to analyse a panel of iron metabolism-related genes (HFE, TFR2, HJV, HAMP, SLC40A1, and FTL) in 87 non-classic HH Portuguese patients. A total of 1241 genetic alterations were detected corresponding to 53 different variants, 13 of which were not described in the available public databases. Among them, ﬁve were predicted to be potentially pathogenic: three novel mutations in TFR2 [two missense (p.Leu750Pro and p.Ala777Val) and one intronic splicing mutation (c.967-1GNC)], one missense mutation in HFE (p.Tyr230Cys), and one mutation in the 5′-UTR of HAMP gene(c.-25GNA). The results reported here illustrate the usefulness of NGS for targeted iron metabolism-related gene panels, as a likely cost-effective approach for molecular genetics diagnosis of non-classic HH patients. Simultaneously, it has contributed to the knowledge of the pathophysiology of those rare iron metabolism-related disorders.